Extracellular matrix shapes cancer stem cell behavior in breast cancer: a mini review - Li, Lei; Tang, Yidan; Qiu, Ling; Li, Zhengrui; Wang, Ruo (Frontiers in Immunology, 2025)
Today, cancer has become one of the leading global tragedies. It occurs when a small number of cells in the body mutate, causing some of them to evade the body’s immune system and proliferate uncontrollably. Even more irritating is the fact that patients with cancers frequently relapse after conventional chemotherapy and radiotherapy, leading to additional suffering. Scientists thereby presume that cancer stem cells (CSCs) are the underlying cause of metastasis and recurrence. In recent years, it was shown that not only can chemotherapy and radiotherapy underperform in the treatment of breast cancer, but they can also increase the number of breast cancer stem cells (BCSCs) that transform regular breast cancer cells into their own population. Such data somewhat support the aforementioned hypothesis. Meanwhile, our understanding of the extracellular matrix (ECM) has changed considerably over the last decade. A lot of studies have bit by bit complemented human knowledge regarding how the ECM greatly shapes the behaviors of BCSCs. In this review, we highlighted the influence on BCSCs exerted by different critical components and biochemical properties of ECM.